Link And Match Strategy of Islamic Banking Vocational High School Human Resources with the Islamic Banking Industry - Purnama Putra (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study is to determine the strategy used for Link and Match between Islamic banking vocational schools and the Islamic banking industry. The research method uses a qualitative descriptive analysis, by conducting interviews with the Patriot BPRS in Bekasi City and SMK Negeri 5 Bekasi City, the Islamic Banking Study Program. The analytical technique used in this research is an in-depth technique, namely examining problems on a case-by-case basis because qualitative methodologies believe that the nature of a problem will be different from the nature of other problems. The results of this study indicate that the link and match strategy with Islamic banking has been going well in several fields, namely the curriculum sector, the field of industrial relations recruitment and the field of IQF certification. These three fields aim to train the development of individual competencies in order to keep abreast of developments in the Islamic banking industry. Meanwhile, according to the Islamic banking industry, it is very important to carry out a link and match strategy in order to be able to compete with other competitors who have considerable opportunities in other Islamic financial institutions.